Alphitobius diaperinus (Coleoptera: Tenebrionidae) susceptibility to Cunila angustifolia essential oil - Prado G.P.D.* (2013)
The lesser mealworm, Alphitobius diaperinus (Panzer), is an insect that lives in poultry houses, and high infestations may cause economic losses to producers. The control of this insect is usually done with insecticides; however, many of these chemicals have no effect on lesser mealworm. Therefore, control alternatives are needed. The aim of this study was to evaluate the influence of Cunila angustifolia (Benth) oil on larvae and adults of A. diaperinus. In vitro tests used larvae and adults of A. diaperinus distributed in petri dishes with 0, 1, 5, and 10% of oil in a single dose. In vivo tests were performed in poultry houses with five treatments: 0, 5, and 10% and chemical insecticide (cypermethrin) in a single application, and a group with 5% of oil applied twice 15d apart. In vitro, oil bioactivity showed an efficacy of 100% both for larvae and adults, when tested at concentrations of 5 and 10%. A reduced number of larvae were observed using 1% of oil; however, it was not effective against adults as compared with the control group. In vivo, the oil effectiveness against lesser mealworm was verified by larva and adult reduction in all concentrations compared with control (0%) throughout the experiments, with better efficacy when used at 5% with two applications. Therefore, we concluded that the oil of C. angustifolia has larvicidal and insecticidal effect against A. diaperinus larvae and adults, in vitro and in vivo. © 2013 Entomological Society of America.